Empréstimo entre bibliotecas: situação nas bibliotecas especializadas e universitárias de Belo Horizonte - Bernadete Santos Campello (1984)
This is an atempt to identify the facts that characterized the interlibrary loan activities ín special and university líbraries of Belo Horizonte (Brazil) in the period l980l98l, with emphasis in the following aspects: rationalization and standardization of servíces; distribution of the transactions by area; amount and distribution of the transacticns by libraries; limitations in the use of the of service; diffículties in its execution and the librarians poínt of view on the principles of interlibrary loan. It was found that the service has standardized the use of forms and union catalogues of periodicals. However few institutions have explicit policies for the service; the transactíons are made mainly between libraries in the same locality; the majority of libraries have a low number of transactíons with the largest volume concentrated in a few institutions; there is no practical limitations with regard to the status of readers which use the service and this one is not paid; the main problems found are "communicatíon and transport" and "incomplete bibliographic citation"; the basic orientation seems to be the free access to information. Recommendations were made towards the solution of some problems as well as suggestions for new studies in the area. ·